LAYANAN BIMBINGAN KLASIKAL BERBASIS DARING SELAMA MASA PANDEMIK COVID 19 - Wilda Kamalia; Tri Suyati; Desi Maulia (Dharmas Education Journal (DE_Journal), 2020)
This research is conducted to reveal how the implementation process of providing classical guidance services carried out boldly as an alternative means besides providing face-to-face classical guidance services during the Covid 19 pandemic, the approach applied in this research is qualitative through case research, the data used of this research this was descriptive obtained from the results of observations, interviews and documentation which will later be used as the latest in processing data from informants, then the informant used was the purposive sampling technique by considering certain characteristics or criteria of a counseling teacher who provided a bold-based classical guidance service and two students of SMK Texmaco Semarang class X Fashion Design with an active background and never been absent from participating in bold-based classical guidance services during the Covid 1 9 pandemic. The results showed that classical guidance services that are given courageously could work but were less effective because of various limitations